ІНФОРМАЦІЙНА І РЕГУЛЯТОРНА РОЛЬ РОЗЧИНЕНОЇ У МОРСЬКІЙ ВОДІ ОРГАНІЧНОЇ РЕЧОВИНИ - Єрохін, В. Є.; Кузнєцов, А. В. (Marine Ecological Journal, 2023)
A hypothesis concerning the possible informative and regulatory roles of high molecular DOM components is proposed. As an example of DOM, the epigenetic role for foreign DNA is demonstrated in the model experiments on M. galloprovincialis. A penetration of foreign DNA into mussel’s ova as a result of direct sperm transfection or processing by the carrier DNA:protein:lipids complex is shown. The results suggested a selective binding of foreign DNA with the sperm cells from different individuals. An assumption is made that the transport of foreign DNA by fertilization, as well as its stable inheritance was happened during a gamete’s competence phase, also as a specific combination of their genotypes and epigenetic factors. The competent sperm cells are capable to uptake spontaneously foreign DNA molecules from environment and to keep them in a compartment inaccessible for external DNases. In the case of DNA:protein:lipids, complex, the proteins V-GAL4 and mostly V-GCN4 provide the delivery of pCMVgfp(bind) plasmid into nuclei of mussel’s sperm cells that leads to expression of GFP-protein in larva after fertilization. The conclusion is made, the foreign DNA (plasmids) and their fragments included in DOM are capable to block the fertilization and interfere with the developmental program of mussels. The role of these signals in fertilization and future development is not understood. Probably, DOM carries out the informational and regulatory role, and sperm cells are an extraordinary vector for the epigenetic information. The available data for microorganisms and invertebrates are used in the discussion.